I need help trying to figure out how to solve
log (2-3x) + log (3-2x) = 1.5
logbase7(1-x) - logbase7(x+2) = logbase7(x^2)
Thank You!
Hello,
You know that log(a)+log(b)=log(ab)log (2-3x) + log (3-2x) = 1.5
So
And you can continue by developping what's in brackets and taking the exponential (beware of the domain of the function)
Since , you can transform the previous equation :logbase7(1-x) - logbase7(x+2) = logbase7(x^2)
Since log(a)-log(b)=log(a/b), it's the same as :
And if log(a)=log(b), then a=b